Multimodality Imaging of Pericardial Hematoma - Ajam, Mustafa; Singh, Manmohan; Ali, Abdelrahman; Elder, Zachary; Ajmal, Rasikh; Rashed, Ahmed; Shokr, Mohamed (Cardiology and Cardiovascular Medicine, 2021)
A 66-year-old male, with a history of atrial fibrillation on chronic anticoagulation therapy, and a known pericardial hematoma, presented to the hospital with worsening dyspnea initially attributed to right sided pleural effusion. Further imaging with Computed Tomography (CT) scan of the thorax and Transthoracic Echocardiography (TTE) revealed enlarging mass-like pericardial lesion with scattered calcifications compressing the right ventricle. Contrast echocardiography demonstrated prominent contrast enhancement and vascularity raising the concern for a malignant nature of the pericardial lesion. Positron Emission Tomography (PET) scan of the myocardium did not reveal any metabolic activity of the lesion. Eventually a biopsy of the lesion was obtained, and it confirmed the diagnosis of a pericardial hematoma. This report highlights the utility of the current cardiac imaging modalities in the evaluation and diagnostic work up of pericardial hematomas.